Social media pressure and the body dysmorphic disorder tendency in women: The mediating role of perfectionism - Sulistyo, Putri Talitha Salsabila; Sukamto, Monique Elizabeth; Ibrahim, Nada (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
The ideal body image displayed in social media often makes women vulnerable to body image issues, one of which is body dysmorphic disorder (BDD). This study aims to examine the role of social media pressure in predicting the tendency towards such a disorder in emerging adult women, with each of the three dimensions of perfectionism as a mediator. The participants were 385 women aged 18-25 years who used social media and were selected using the convenience sampling technique. Data were collected using the Body Dysmorphic Disorder Screening Scale, Social Media Pressure Scale, Almost Perfect Scale-Revised (APS-R), and some open-ended questions distributed online through various social media. The BDD tendency model tested using structural equation modeling has a good fit with the data (χ2/df = .019, RMSEA = .001, CFI = 1.00) and shows that the role of social media pressure in women's BDD tendency was fully mediated through the discrepancy dimension of perfectionism. The findings indicate that a program is needed to develop media literacy and promote positive body images for women who use social media to prevent body image issues.